First wild record of Dendrochilum warrenii (Orchidaceae: Epidendroideae) confirms a Philippine provenance - Naive, Mark Arcebal K. (Universidad de Costa Rica, 2018)
Recent explorations on one of the mountains of the Bukidnon province on the island of Mindanao in the Philippines resulted in a wild collection of Dendrochilum warrenii, an Orchidaceae species described in 2004 from a cultivated plant of unknown provenance. In this publication, an extended species description along with color photographs are provided to aid future identification. Information on the distribution, ecology and phenology of the species in the wild is also provided.